2018
DOI: 10.5582/irdr.2018.01041
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic neuroma as a rare cause of intractable neuropathic breast pain following cancer surgery: Management and review of the literature

Abstract: Traumatic neuroma of the breast after cancer surgery is a very rare clinical entity with only a few cases having been reported to date. We herein present a very rare case of traumatic breast neuroma in a postmenopausal patient with a history of breast-conserving surgery, who presented with a four-month history of intractable neuropathic breast pain. Diagnostic evaluation and management are discussed along with a review of the literature. Traumatic breast neuromas are very rare benign lesions that have been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Patients were either asymptomatic or complained of pain, tenderness, or extreme pain during aspiration. [7,11] The mechanisms of neuroma-associated pain are not fully understood. Some research has indicated that increasing levels of nerve growth factor, alpha-smooth muscle actin, cannabinoid CB2 receptor, and unmyelinated fiber, as well as changes in peripheral and central sensitization, may be related to neuroma-associated pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were either asymptomatic or complained of pain, tenderness, or extreme pain during aspiration. [7,11] The mechanisms of neuroma-associated pain are not fully understood. Some research has indicated that increasing levels of nerve growth factor, alpha-smooth muscle actin, cannabinoid CB2 receptor, and unmyelinated fiber, as well as changes in peripheral and central sensitization, may be related to neuroma-associated pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, 4 lesions exhibited indistinct margin and irregular shape, [3,10] 2 lesions in 1 patient demonstrated inner vascularity, [10] and one 0.2-cm lesion was unremarkable in a surgical scar after breast-conserving surgery. [11] The tail sign was described in 2 reports with an incidence of 33.3% to 50%. [7,10] Nonetheless, this sign was absent in our cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this process can expand and intensify. If the axons are unable to grow into existing nerve sheaths or if they encounter obstacles on their path, such as a scar or an amputated end of a nerve, they grow chaotically as a small tumour -a neuroma -which is very sensitive to mechanical damage and can cause increased pain [10,11].…”
Section: Pathomechanism Of Neuropathic Painmentioning
confidence: 99%
“…Co więcej, proces ten może się rozszerzać i być coraz bardziej intensywny. Jeżeli aksony nie są w stanie wrosnąć w istniejące osłonki nerwowe albo na swojej drodze napotykają przeszkody, takie jak blizna lub koniec nerwu jest amputowany, aksony rosną chaotycznie w postaci niewielkiego guzka -nerwiaka (neuroma), który jest bardzo wrażliwy na uraz mechaniczny i może być przyczyną nasilonego bólu [10,11].…”
Section: Patomechanizm Bólu Neuropatycznegounclassified